Lifestyle modification practice and associated factors among diagnosed hypertensive patients in selected Hospitals in West Arsi Zone, Oromia Regional State, Ethiopia - Wakjira, Hika; Gobena, Tesfaye; Shore, Hirbo (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: Globally 1.13 billion people were living with hypertension, Out of this two-thirds of them were living in low and middle-income countries. In Ethiopia, Non-Communicable Disease deaths are estimated at around 42%. However, it remains widely undetected and poorly controlled. To resolve these, lifestyle modification approaches that are often overlooked are the cornerstone of the prevention and management of hypertension. Objective: To assess lifestyle modification practice and associated factors among hypertensive patients in selected hospitals in West Arsi Zone, Oromia Regional, Ethiopia December 7 to 21, 2019. Method: Hospital-based cross-sectional study was conducted in the selected public hospital among 299 hypertensive patients. Systemic random sampling methods were used to select the study participants. Data were collected by face-to-face interviews using a structured questionnaire by trained data collectors. Data were analyzed using descriptive statistics and multivariate logistic regression method to identify predictors of the outcome (p < 0.05). Results: Of the total participants, only 25.2% (95% CI: 18.8-32.9) of the patients were practiced recommended lifestyle modifications. Patients Age older than 65 years (AOR = 2.9, 95% CI: 1.17 - 7.0), the patients with 2-5 years’ time since diagnosed hypertension (AOR = 0.26, 95% CI: 0.07 - 0.9), multiple co-morbidity (AOR = 2.7, 95% CI: 1.25 - 5.8,) and their knowledge on hypertension management (AOR = 14.6, 95% CI: 4.6 - 45.9) have an independently associated with recommended lifestyle modification. Conclusion: Lifestyle modification practices among hypertensive patients were low in this study. Age, comorbidity, time since diagnoses of hypertension, and knowledge of lifestyle were identified as predictors of the outcome.